(untitled) (Research, Society and Development, 2020)
The objective of this study was to evaluate the effects of the cultivation and decomposition of cover crops on the growth and production of biomass of pink pepper grown in succession. The pre-cultivation treatments consisted of four species of green manure (cajanus; pork beans; crotalaria; mucuna). The treatments were arranged in a randomized block design with six replications. The field evaluations consisted of quantifying the fresh and dry biomass of the aerial part of the different species of green manure. Four whole plants were harvested per plot, of the pink pepper, to evaluate the averages of production of fresh and dry mass of the aerial part and roots. The data obtained were subjected to analysis of variance and, when significant by the F test (p <0.05), the means were compared by Tukey. It was concluded that the black mucuna, cajanus, pork bean and crotalaria are alternatives as green manure in the cultivation of pink pepper in succession. The best performance of pink pepper in terms of biomass production occurred in succession to mucuna. Only the analysis of biomass accumulation by green manure and the successor plant is insufficient to guide the choice of a production system.